KOMUNIKASI DALAM PERTUNJUKAN DRAMA: ANTARA PENGARANG, AKTOR, DAN PENONTON - Arif Hidayat (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Actor's competency to act in a drama performance can improve his ability to perform good communication. In addition,drama, as a performance art, can give an enlightening process to the audience through the values contained in the dialogues. As aresult, drama develops well, reaching the areas of countryside and also in universities, which usually called "teater kampus (collegetheater)". Drama is also included in the curriculum of literary study. This paper describes the communication between drama and itsaudience.